The use of prescribed fire in Portugal as a tool for forest management - Meira Castro, Ana C. (2017)
Prescribed fires in forest areas are frequently used in most Mediterranean countries as a preventive technique to avoid several wildfires in the summer season. In Portugal this forest management pratice is a common tool used for biota control and for reduction of forest fuel mass availability, and therefore to promote the reduce of wildfire occurrence and a shorter fire suppression effort. Although the use of precribed fire has been shown to be beneficial - as annual statistical reports confirm the the decrease of wildfires accurrence has a direct relationship with the controlled fire practice - serious side effects, in some forest soil properties, were also reported. Taking in consideration the pros and cons, ICNF - the Portuguese Institute of Nature and Forest Conservation - still adopts the use of prescribed fires nowadays as a tool for the maintenance of forest sustainability. In this work, we describe the use of prescribed fire in Portugal under a forest management perspective and we reflect over the evolution of the term forest sustainability in the last decades and how it played an important role on forest management options.